Shipping lines' perspective in container terminal investments - Xu, Jiawei (2014)
Since 1960s, shipping lines have shown their interests in owning and operating container terminals. The interests extend all the way into 21st century. However, there is an increasing trend of container lines divesting their owning terminals, especially during the recent economic downturn since 2008.